Reviews of recent publications - various authors (Studies in 20th & 21st Century Literature, 1993)
Granqvist, Raoul, editor. Canonization and Teaching of African Literature. Matatu 7 by Claire L. Dehon Margolis, Joseph. Texts Without Referents: Reconciling Science and Narrative by David J. Depew Keitel, Evelyne. Reading Psychosis, Readers, Texts and psychoanalysis by Reinhild Steingrover Shaviro, Steven. Passion and excess: Blanchot, Bataille, and Literary Theory by Steven Ungar Kellner, Douglas. Jean Baudrillard From Marxism to Postmodernism and Beyond by Allan Stoeld Pecorora, Vincent P. Self & Form in Modern Narrative by Walter A. Strauss Jordan, Barry. Writers and Politics in Franco's Spain by Salvador J. Fajardo Motard-Noar, Martine. Les Fictions d'Hélène Cixous. Une autre lanque de femme by Randi Brox Birn Alexandrov, Vladimir E. Nabokov's Otherworld by Dale E. Peterson Baker, Peter. Obdurate Brilliance: Exteriority and the Modern Long Poem by Steven Winspur
Keywords: Raoul Granqvist; Canonization and Teaching of African Literature. Matatu 7; Joseph Margolis; Texts Without Referents: Reconciling Science and Narrative; Evelyne Keitel; Reading Psychosis Readers Texts and psychoanalysis; Steven Shaviro; Passion and excess: Blanchot Bataille and Literary Theory; Douglas Kellner; Jean Baudrillard From Marxism to Postmodernism and Beyond; Vincent P. Pecorora; Self & Form in Modern Narrative; Barry Jordan; Writers and Politics in Franco' s Spain; Martine Motard-Noar; Les Fictions d' Hélène Cixous. Une autre lanque de femme; Vladimir E. Alexandrov; Nabokov' s Otherworld; Peter Baker; Obdurate Brilliance: Exteriority and the Modern Long Poem; Claire L. Dehon; David J. Depew; Reinhild Steingrover; Steven Ungar; Allan Stoeld; Walter A. Strauss; Salvador J. Fajardo; Randi Brox Birn; Dale E. Peterson; Steven Winspur